Cross-Validation and Validation Set Methods for Choosing K in KNN Algorithm for Healthcare Case Study - Robbi Rahim; Ansari Saleh Ahmar; Rahmat Hidayat (PT Mattawang Mediatama Solution, 2022)
KNN categorization is simple and successful in healthcare. In this research's example case study, the KNN algorithm classified the new record as